ISLAMIC BOARDING SCHOOLS, AGRIBUSINESS MICRO ECONOMICS AND ECONOMIC EMPOWERMENT STRATEGIES - Villatus Sholikhah (FORPIM PTKIS ZONA TAPAL KUDA, 2022)
ABSTRACTThis study aims to describe the strategy of pesantren in empowering the community agribusiness economy. The research method uses qualitative and the type of research uses library research. The results of his research indicate that the strategies of pesantren in empowering the community agribusiness economy are: 1) planning, organizing and analyzing the economic potential of community agribusiness and pesantren. The economic potential of the community is in the form of HR, Physical, Connections and so on. Analyzing this potential can take the form of a SWOT analysis; 2) implementing community agribusiness economic empowerment programs. This implementation involves all the potentials possessed by the community and pesantren; 3) monitoring and evaluating community agribusiness economic empowerment programs. This monitoring is carried out during economic empowerment activities. Evaluation can be done while the activity is in progress or when the activity has been completed. This process is carried out to ensure that the accountability and transparency processes run well.Keywords: Islamic Boarding School, Agribusiness, Economic Empowerment Strategy